2020
DOI: 10.1113/jp276544
|View full text |Cite
|
Sign up to set email alerts
|

Designer genetically encoded voltage‐dependent calcium channel inhibitors inspired by RGK GTPases

Abstract: High-voltage-activated calcium (Ca V 1/Ca V 2) channels translate action potentials into Ca 2+ influx in excitable cells to control essential biological processes that include; muscle contraction, synaptic transmission, hormone secretion and activity-dependent regulation of gene expression. Modulation of Ca V 1/Ca V 2 channel activity is a powerful mechanism to regulate physiology, and there are a host of intracellular signalling molecules that tune different aspects of Ca V channel trafficking and gating for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 78 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…ELKS binding to β 2 subunit in pancreatic β-cells enhanced L-type Ca 2+ current at the vascular side of the β-cell plasma membrane and regulated the initial polarized Ca 2+ influx and rapid insulin vesicle exocytosis [152]. Another important mechanism that dynamically modulates the HVCC membrane incorporation and function is the interaction of the β and α 1 subunits with the small GTPases RGK protein family members (Rem, Rem2, Rad, Gem/Kir) [153]. Initially it has been shown that co-expression of Gem with Ca V 1.2 or Ca V 1.3 channels resulted in Ca 2+ influx inhibition, and these findings were later extended to the other RGK family members (Rad [154], Rem and Rem2 [155,156], Gem [157,158]) and HVCC isoforms [156,159].…”
Section: β-Subunitsmentioning
confidence: 99%
“…ELKS binding to β 2 subunit in pancreatic β-cells enhanced L-type Ca 2+ current at the vascular side of the β-cell plasma membrane and regulated the initial polarized Ca 2+ influx and rapid insulin vesicle exocytosis [152]. Another important mechanism that dynamically modulates the HVCC membrane incorporation and function is the interaction of the β and α 1 subunits with the small GTPases RGK protein family members (Rem, Rem2, Rad, Gem/Kir) [153]. Initially it has been shown that co-expression of Gem with Ca V 1.2 or Ca V 1.3 channels resulted in Ca 2+ influx inhibition, and these findings were later extended to the other RGK family members (Rad [154], Rem and Rem2 [155,156], Gem [157,158]) and HVCC isoforms [156,159].…”
Section: β-Subunitsmentioning
confidence: 99%
“…Of note, this was also seen in differences between Gem-mediated inhibitory effects. RGK-proteins have been proposed to have potentials as therapeutic tools for a differential and specific modulation of VGCCs (Colecraft 2020 ). It is tempting to speculate that RGK proteins might be a tool to differentially compensate for changes of VGCC-mediated currents that are due to mutated Ca V β subunits.…”
Section: Discussionmentioning
confidence: 99%
“…The development of genetically encoded Ca V channel inhibitors has been one of the foci of the Colecraft lab for many years [ 145 ]. Understanding the mechanisms by which RGK proteins inhibit Ca V channels has allowed them to engineer RGK proteins that specifically inhibit subtypes of Ca V channels in cardiomyocytes and in neurons, i.e.…”
Section: Endocytosis and Recycling Of Ca Vmentioning
confidence: 99%